2000
DOI: 10.1109/66.857933
|View full text |Cite
|
Sign up to set email alerts
|

Particle characteristics of 300-mm minienvironment (FOUP and LPU)

Abstract: We have clarified the particle characteristics of a front opening unified pod (FOUP) and a load port unit (LPU) experimentally. The FOUP and LPU are fundamental components in 300-mm minienvironment systems. Our experiments showed the following.• The particles per wafer pass (PWP) increases with the number of airborne particles outside the enclosure. • The particle characteristics of FOUP and LPU can be improved by reducing the FOUP door-opening speed. • The PWP of the wafer in the top slot is remarkably high. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kobayashi et al (2000) performed PWP testing on particles with diameters ≥0.12 µm, for wafers in the FOUP during the opening of the FOUP door. They reported that the PWP value of the top wafer (wafer 25) is the highest.…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al (2000) performed PWP testing on particles with diameters ≥0.12 µm, for wafers in the FOUP during the opening of the FOUP door. They reported that the PWP value of the top wafer (wafer 25) is the highest.…”
Section: Introductionmentioning
confidence: 99%